Efficient and air-stable mixed-cation lead mixed-halide perovskite solar cells with n-doped organic electron extraction layers - Wang, Z; McMeekin, D; Sakai, N; van Reenen, S; Wojciechowski, K; Patel, J; Johnston, M; Snaith, H (Wiley, 2016)
Air-stable doping of the n-type fullerene layer in an n-i-p planar heterojunction perovskite device is capable of enhancing device efficiency and improving device stability. Employing a (HC(NH2 )2 )0.83 Cs0.17 Pb(I0.6 Br0.4 )3 perovskite as the photoactive layer, glass-glass laminated devices are reported, which sustain 80% of their "post burn-in" efficiency over 3400 h under full sun illumination in ambient conditions.